Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A mechanistic, distributed model for coupled simulation of soil water-plant, groundwater and surface flow system in arid/semi-arid agricultural watersheds (SurfMOD)—Model description and evaluation - Danning Mu; Xu Xu; Xue Xiao; Tiago B. Ramos; Chen Sun; Xinyi Li; Yihao Xun; Guanhua Huang (Journal of Hydrology, 2025)

Eco-grease from upcycling of waste oils: a formulation study for high-performance lubricants - N. A. F. Bashari; M. A. A. Aziz; M. A. Hairunnaja; T. M. A. B. N. Mu’Tasim (International Journal of Environmental Science and Technology, 2025)
The disposal of waste oils, particularly waste engine oil (WEO) and waste turbine oil (WTO), presents serious economic and environmental issues due to their high contamination and degradation levels, which reduce the efficiency of direct reuse or conventional recycling. This study investigates a practical approach for upcycling WTO and WEO into high-performance lubricating grease, providing a sustainable substitute for petroleum-based lubricants. The study includes five essential stages: waste oil collection, pre-treatment, characterization, grease formulation, and performance assessment. Following treatment, the viscosity, elemental content, and moisture levels of the oils complied with Department of Environment (DOE) and ASTM D5185 standards, confirming their viability as base oils. The formulated greases achieved NLGI grades of 2–3, oil bleed percentages within a ± 15%, and oil separation below 4%. They also exhibited low coefficients of friction (0.062–0.133) and wear scar diameters ranging from 415.65 to 866 μm. These results confirm that treated WTO and WEO can be converted into greases with performance comparable to conventional products, supporting reduced dependence on virgin base oils. The formulations were assessed under relevant ASTM and NLGI standards. Future work may explore additives or scale-up approaches to enhance long-term performance and market readiness.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A Future of Self-Directed Patient Internet Research: Large Language Model-Based Tools Versus Standard Search Engines - Arya Rao; Andrew Mu; Elizabeth Enichen; Dhruva Gupta; Nathan Hall; Erica Koranteng; William Marks; Michael J. Senter-Zapata; David C. Whitehead; Benjamin A. White; Sanjay Saini; Adam B. Landman; et al. (Annals of Biomedical Engineering, 2025)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A Graph Convolutional Network Approach to Qualitative Classification of Hydrocarbon Zones Using Petrophysical Properties in Well Logs - B. Venkateshwaran; Mu. Ramkumar; Numair Ahmed Siddiqui; AKM Eahsanul Haque; G. Sugavanam; A. Manobalaji (Natural Resources Research, 2024)

Genetic diversity of the Atacama Desert shrub Huidobria chilensis in the context of geography and climate - K. Bechir Ferchichi; T. Böhnert; B. Ritter; D. Harpke; A. Stoll; P. Morales; S. Fiedler; F. Mu; J. Bechteler; C. Münker; M.A. Koch; T. Wiehe; et al. (Global and Planetary Change, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

A prospective observational phase IV study on effectiveness of animal derived polyclonal antibody antivenoms against West African carpet viper (Echis romani) induced coagulopathy and mortality - Titus B. Dajel; Saidu B. Abubakar; Nasiru M. Dan-Amarya; Nyam A. Azi; Salisu Mu'azu; Muhammad Hamza; Garba Iliyasu; Muhammad Y. Gwarzo; Abdulrazaq G. Habib (Toxicon, 2023)

Divergent structures of Mammalian and gammaherpesvirus uracil DNA glycosylases confer distinct DNA binding and substrate activity - Yunxiang Mu; Monika A. Zelazowska; Zaowen Chen; Joshua B. Plummer; Qiwen Dong; Laurie T. Krug; Kevin M. McBride (DNA Repair, 2023)

Effects of grouting cycle and aeration on sand strengthening with ureolytic bacteria - J. Xu; B. Mu; J. Chen; J. Zuo (International Journal of Environmental Science and Technology, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

Repurposed FDA-approved drugs targeting genes influencing aging can extend lifespan and healthspan in rotifers - Terry W. Snell; Rachel K. Johnston; Amelia B. Matthews; Hongyi Zhou; Mu Gao; Jeffrey Skolnick (Biogerontology, 2018)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Modulation of high impulsivity and attentional performance in rats by selective direct and indirect dopaminergic and noradrenergic receptor agonists - Anushka B. P. Fernando; Daina Economidou; David E. Theobald; Mu-Fa Zou; Amy H. Newman; Marcia Spoelder; Daniele Caprioli; Margarita Moreno; Lucia Hipόlito; Albert T. Aspinall; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2012)

Impacts of soil conservation on groundwater recharge in the semi-arid Loess Plateau, China - John B. Gates; Bridget R. Scanlon; Xingmin Mu; Lu Zhang (Hydrogeology Journal, 2011)

Sequence characterization and promoter identification of porcine APC10 gene - W. B. He; Z. W. Wang; Y. Li; Z. L. Tang; S. L. Yang; Y. L. Mu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

A pilot study on the association between job stress and repeated measures of immunological biomarkers in female nurses - Kyoung-Mu Lee; Daehee Kang; Kijung Yoon; Sun-Young Kim; Ho Kim; Hyung-Suk Yoon; Douglas B. Trout; Joseph J. Hurrell (International Archives of Occupational and Environmental Health, 2010)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Metal Concentrations in Soil in the Vicinity of a Municipal Solid Waste Landfill with a Deactivated Medical Waste Incineration Plant, Ribeiro Preto, Brazil - S. I. Segura-Muoz; A. Bocio; T. M. B. Trevilato; A. M. M. Takayanagui; J. L. Domingo (Bulletin of Environmental Contamination and Toxicology, 2004)

Trace Metal Distribution in Surface Soil in the Area of a Municipal Solid Waste Landfill and a Medical Waste Incinerator - S. I. Segura-Muoz; A. M. M. Takayanagui; T. M. B. Trevilato; C. B. Santos; S. E. Hering (Bulletin of Environmental Contamination and Toxicology, 2004)

A phylogenetic analysis of basal metabolism, total evaporative water loss, and life-history among foxes from desert and mesic regions - J. B. Williams; A. Muoz-Garcia; S. Ostrowski; B. I. Tieleman (Journal of Comparative Physiology B, 2004)

Resistance of Salmonella and Campylobacter Species to Antimicrobial Agents - B. Mirelis; G. Prats; T. Llovet; C. Muoz; F. Navarro (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)